Simple electrode configurations for probing deep organs using Electrical Bio-Impedance techniques - Rabbani, K Siddique e (Bangladesh Journal of Medical Physics, 2019)
Tetrapolar Impedance Method (TPIM) and Focused Impedance Method (FIM) are two simple modalities of electrical bio-impedance measurement that could be employed to give useful physiological and diagnostic information of the human body. FIM is based on TPIM but uses a combination of two sets of TPIM, producing a focusing effect, which is useful to localize specific target organs. Most non-invasive electrical bio-impedance measurements based on TPIM and FIM use electrodes on one side of the body, outside the skin surface, which gives a shallow depth sensitivity. The sensitivity decreases with depth so that deep organs like lungs, heart, liver, stomach and bladder are not fully assessed through such measurements. Based on a long experience of studying electrical impedance methods, several qualitative ideas are presented in this article for probing deep organs using a few modified TPIM and FIM configurations. The suggestions are based on visualisations of both equipotentials and a popular sensitivity equation for transfer impedance, but not based on any quantitative analysis. Simulation and phantom studies based on these ideas may produce some practically useful electrode configurations for real life bio-impedance measurements. Bangladesh Journal of Medical Physics Vol.11 No.1 2018 P 1-15